Use of Space Syntax Technique to Improve the Quality of Lighting and Modify Energy Consumption Patterns in Urban Spaces - Kazemidemneh, Maryam; Mahdavinejad, Mohammadjavad (European Journal of Sustainable Development, 2018)
Urban lighting is one of the significant issues that urban designers and architects are facing, and it has received a special attention in recent years. Urban lighting pursues critical goals such as preserving the livability of the city during nighttime, providing a sense of security, maintaining the city?s readability, etc. Use of incompatible patterns for lighting design wastes significant amount of energy annually. A master lighting plan for urban areas should be recommended to achieve these goals and prevent wasteful energy use in lighting. One of the solutions for designing an appropriate plan is to notice the pedestrian traffic pattern in the city by considering space syntax model and integration maps analysis. In this research, one of Tehran?s regions has been chosen and its integration map has been generated using appropriate software. Tehran is selected as case study of this research while the results might be applied in other similar cities especially in developing countries. First, based on the integration degree of the passages which reveals pedestrian traffic pattern and considering recommended illuminance standards, the average required lighting has been determined. Second, comparing the measured lighting intensity and the standard amounts reveals the correlation between the presented urban lighting and energy consumption model. Eventually, different solutions for appropriate urban lighting design based on acceptable energy consumption patterns have been suggested. Keywords: lighting design, space syntax, integration analysis, energy consumption, Sustainable Development